Improvement of Road Infrastructure for Agricultural Areas in Rawang Panca Arga District on Regional Resilience in Asahan Regency - Irfan; Abdi Sugiarto; Cut Nuraini (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study aims to examine the Improvement of Road Infrastructure for Agricultural Areas in Rawang PancaArga District against Wlayah Resilience in Asahan Regency. This research uses a qualitative approach to exploreand understand the experiences, perceptions, and dynamics that occur in the community related to roadinfrastructure and its impact on agricultural areas and regional resilience. The research was conducted inRawang Panca Arga District, Asahan Regency, which is an area with significant agricultural potential andinfrastructure challenges that need to be overcome. In-depth Interview Data Collection Techniques: Following asemi-structured interview guide that allows informants to share their experiences with flexibility in answering,Validity and Reliability: The validity of the data will be guaranteed through triangulation, i.e. by comparing datafrom different sources and methods to ensure consistency and accuracy of information. Overall, the improvementof road infrastructure in Rawang Panca Arga District supports the resilience of the Asahan Regency area througheconomic strengthening, food security, emergency preparedness, and long-term investment development. Thisdiscussion shows that adequate road infrastructure is one of the key factors in strengthening regional resilienceas a whole, supporting economic growth, and improving the welfare of local communities.